Evaluation of Wheat Seed Traits Stored in Outdoor Before Processing - H. Khazaei (علوم و فناوری بذر ایران, 2016)
In order to compare the seed characteristics of wheat seed lots stored in outdoor, a factorial experiment based on a completely randomized design with three replications was carried out at three wheat seed purchasing and processing centers located in Mashhad, Torbat-e-Heydaryie and Torbat-e-Jam for one year from June 2005. The First factor was three wheat varieties including Falat, Chamran, Cascojen and the second factor was duration of wheat seed storage in outdoor for 0, 15, 30 and 45 days before processing. Moisture content, hectolitre weight, seed loss percentage while processing, germination percentage before and after accelerated aging test, seedling vigor index and germination rate were evaluated. Accelerated aging test was done before determine the germination percentage, seedling vigor index and germination rate test. Compound analysis of variance for locations showed that effect of variety in moisture content and seedling vigor index was significant, and the effect of  storage duration except for hectolitre weight in all traits were also significant. Between the time of purchase until 45 days after it, seed loss percentage increased  about 1.9 percent and moisture content and germination percentage were decreased before and after accelerated aging test, also seedling vigor index and germination rate were exposed to a reduction by 5.11, 4.89, 10.26 percent and 314.41, 0.036 unit, respectively. In addition cv. Chamran was less tolerate to outdoor storage conditions compared to Cascojen and Falat.